The effects of nanoscale confinement on the behavior of metal laminates. (October 2020) - Demkowicz, Michael J.; Beyerlein, Irene J.
Abstract: By reducing the layer thickness, h, in metal multilayers from micrometer- to nanometer-levels, scale-dependent transitions in behavior are observed. The role of interface properties in these transitions has been extensively investigated. However, reducing h to the nanoscale regime also imposes a physical geometric confinement on defect-related processes occurring within the layers, an effect that is less explored. We present illustrative examples of the influence of nanoconfinement on the strength, structure, and radiation response of multilayers. These examples show that nanoconfinement and interface structure and topology act cooperatively in the nanoscale limit, affecting behaviors that cannot be explained based on either factor alone.